(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
Indigenous tourism refers to tourism activities that increase association between tourist, and local people of that area, they linked their self with historical sites, culture, and traditions. The study is about the impacts of tourism on community development and how it contributes to cultural preservation. The applied theory in the study is theory of modernization is given by Rostow Winton in 1954, talks about how society develop from a precondition era to takeoff situation that improves economic development through tourism. The study add value to UN SDG 8, target 8.9. The research is based on a small province Gilgit Baltistan, Pakistan. It is a qualitative study from lens of content analysis, it follows the micro (individual) level approach. The results of research shows that indigenous tourism has more positive impact on community development, especially in form of preservation of cultural historical sites, economic development and provide different opportunities to local communities. It has undesirable impact on environment which brings climate change in the region. The communities’ control over their own natural resources and use their cultural as a strength to promote tourism and increase the notion of hospitality among the residents. Communities globally have been successful maintaining their culture with tourism because it helps sustainability. The study is significant as it highlights the dual impact of indigenous tourism on community development and cultural preservation while addressing environmental concerns.